Activated Mesenchymal Stromal Cell Therapy for Treatment of Multi-Drug Resistant Bacterial Infections in Dogs - Johnson, Valerie; Chow, Lyndah; Harrison, Jacqueline; Soontararak, Sirikul; Dow, Steven (Frontiers in Veterinary Science, 2022)
New and creative approaches are required to treat chronic infections caused by increasingly drug-resistant strains of bacteria. One strategy is the use of cellular therapy employing mesenchymal stromal cells (MSC) to kill bacteria directly and to also activate effective host immunity to infection. We demonstrated previously that activated MSC delivered systemically could be used effectively together with antibiotic therapy to clear chronic biofilm infections in rodent models. Therefore, we sought in the current studies to gain new insights into the antimicrobial properties of activated canine MSC and to evaluate their effectiveness as a novel cellular therapy for treatment of naturally-occurring drug resistant infections in dogs. These studies revealed that canine MSC produce and secrete antimicrobial peptides that synergize with most classes of common antibiotics to trigger rapid bactericidal activity. In addition, activated canine MSC migrated more efficiently to inflammatory stimuli, and secreted factors associated with wound healing and fibroblast proliferation and recruitment of activated neutrophils. Macrophages incubated with conditioned medium from activated MSC developed significantly enhanced bactericidal activity. Clinical studies in dogs with chronic multidrug resistant infections treated by repeated i.v. delivery of activated, allogeneic MSC demonstrated significant clinical benefit, including infection clearance and healing of infected tissues. Taken together, the results of these studies provide new insights into antimicrobial activity of canine MSC, and their potential clinical utility for management of chronic, drug-resistant infections.